2021
DOI: 10.3906/sag-2004-330
|View full text |Cite
|
Sign up to set email alerts
|

Nontraumatic coma in the pediatric intensive care unit: etiology, clinical characteristics and outcome

Abstract: Non-traumatic coma in the pediatric intensive care unit: etiology, clinical characteristics and outcome ABSTRACT Background/aim: The purpose of this study was to evaluate the etiology, clinical characteristics and outcome of non-traumatic coma (NTC) among children admitted to a Pediatric Intensive Care Unit (PICU). Materials and methods: A total of 159 children with NTC were included in the study. The Modified Glasgow Coma Scale (GCS) was used to assess consciousness. Patients were classified with regard to et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 31 publications
1
6
1
Order By: Relevance
“…The remaining three had no evidence of meningitis or BSI and had a favorable outcome. These findings contrast with those from other parts of the world where non-infectious (metabolic, vascular) etiologies of comas are more prevalent [ 15 , 16 ].…”
Section: Discussioncontrasting
confidence: 75%
“…The remaining three had no evidence of meningitis or BSI and had a favorable outcome. These findings contrast with those from other parts of the world where non-infectious (metabolic, vascular) etiologies of comas are more prevalent [ 15 , 16 ].…”
Section: Discussioncontrasting
confidence: 75%
“…These etiologies are slightly different than those found in Turkey where hypoxic ischemic encephalopathy was as common as CNS infections. [19][20][21][22] In accordance with Gwer et al, 23 our study showed that viral encephalitis was the most common CNS infection. This differs from other studies that revealed a higher frequency of acute bacterial meningitis.…”
Section: Discussionsupporting
confidence: 87%
“…leeding is an important cause of preventable death in children (1)(2)(3). Reported 28-day mortality rates in children with life-threatening bleeding range from 36% to 50% (4,5), substantially higher than the mortality rates for nonbleeding pediatric cohorts with comparable illness severity (8-16%) (6)(7)(8) and the mortality rates reported in injured adults with life-threatening bleeding (21-24%) (9,10). Hemostatic resuscitation has evolved over recent decades to include early blood product transfusion, avoidance of crystalloid, prevention of coagulopathy, hypothermia, hypocalcemia and acidosis, and surgical or interventional control of bleeding when applicable (11,12).…”
mentioning
confidence: 99%